Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Problem Solving pada Materi Sistem Ekskresi Manusia Kelas XI SMA/MA - City Qurnia Sari Pohan; Kartika Manalu; Reflina (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
This examination aims to determine the validity, reasonableness and appropriateness of critical thinking prepared by students' worksheets regarding the human excretory framework material for class XI senior high schools in educational experiences. This exam uses Innovative work (RnD) research techniques with a 4D model (Define, Design, Development, and Dissemination). which is adjusted to 3D (Define, Design, and Development). Exploratory instruments use consent forms, surveys and critical thinking skills tests. The consequences of this exploration show that the critical thinking-based student worksheet that has been created is valid and suitable to be applied with a level of 83.3% (material experts) with the